Identification of Pathogenecity of Avian Influenza Virus Subtype H5N1 from Waterfowls Base on Amino Acid Sequence of Cleavage Site Hemagglutinin Protein - R. Susanti; Retno D. Soejoedono; I Gusti Ngurah K Mahardika; Wayan T I Wibawan; Maggy T Suhartono (Universitas Gadjah Mada, 2008)
Identification of pathotype of Avian Influenza Virus (AIV) subtype H5N1 isolates is very important. Thisresearch aimed to identify the pathotype of AIV subtype H5N1 isolated from household waterfowls in West Javabased on molecular markers of amino acid sequences of the Hemagglutinin (HA) cleavage site. Fragments of HAgenes of 21 isolates were amplified using RT-PCR with a primer pair that flanking the cleavage site region, andsequenced with dideoxy-termination method with ABI automatic sequencer (Applied Biosystems). Multiple alignmentof nucleotide and their deduced amino acid sequence were analyzed using ClustalW from MEGA 3.1 program.The result shows that all H5N1 isolates (21 isolates) possess polybasic cleavage sites with 2 patterns ofamino acid sequence, i.e QRERRRKKR (20 isolates) and QRESRRKKR (1 isolate). This finding indicates that all ofthe viruses isolated in this research were of highly pathogenic avian influenza (HPAI) strains.Keywords: cleavage site, waterfowls, HPAI